I feel safe doing it! Prevalence, risk perception and motives for risky driving in Portugal - Duarte, A. P. (2019)
Introduction: Road traffic injuries are among the top 10 causes of death and thus a major public health issue worldwide. Consistent differences between countries in the European Union justify a closer examination of the problem at a national level. The present study focused on identifying the socio-psychological factors behind risky driving, which can help interventions more successfully foster safer driving practices in Portugal. More specifically, this research ana-lysed the prevalence of self-reported risky driving behaviours and their association with perceived risks to establish whether this relationship differs across risk-taking practices. The study also examined drivers' motives for taking risks. Methods: A telephone survey about road safety collected responses from 635 adult drivers. The respondents provided sociodemographic information so comparisons could be made between groups of drivers based on age, gender, and frequency of driving. Results: The risky driving practices most frequently reported by Portuguese drivers were speeding and disregarding the need for rest breaks. The respondents also evaluated these two practices as the least risky, suggesting that drivers minimise their personal risk of traffic accidents. The most frequently mentioned motives for risky driving were a perceived control over vehicles and road conditions. Male, younger, and everyday drivers have higher risk profiles since they reported engaging in risky driving practices more often and perceiving these behaviours as less risky. Conclusion: Portuguese drivers reported engaging consistently in risky driving practices, while evaluating their risk as moderate and their control over driving conditions as high. This contextualised understanding of factors that strengthen the likelihood of risky driving can help facilitate tailor-made interventions to reduce Portuguese drivers' unrealistic perceptions of control and invulnerability, thereby ensuring safer roads.